Estudo da condutividade hidráulica de solos para a disposição de resíduos sólidos na região de Santa Maria - Pinto, Juliane dos Santos (2005)
The study of hydraulic conductivity of soil is an important stage in the geotecnical investigations, aiming at the use of compacted soils as impermeabilizing mineral layers, for the base and cover of sanitary land-fill sites. This paper presents the study of hydraulic conductivity (k) of natural and compacted soils of the Santa Maria region, in the area called Caturrita which was chosen for the future installation of the sanitary land-fill of this city, localized near the current solid waste disposal site of Santa Maria (Robaina, 2002). In this place a detailed geological-geotecnical investigation was undertaken. The objective of this investigation was the identification, classification and characterization of the soils of seventeen drilling profiles (P1 to P17) distributed in the area of study; the majority were executed with a manual boring-tool, of which samples were collected for laboratory tests. For all profiles characterization tests were performed (Atterberg limits, granulometric analysis, density of grains). In one typical profile (P1) complementary tests were made such as, chemical tests, X-ray diffraction, compaction and hydraulic conductivity tests with of rigid and flexible walls permeameters. For this study of hydraulic conductivity a flexible wall permeameter with a simplified triaxial chamber was assembled similar to that of Bjerrum and Huder (1957). In situ tests were performed of the following type: infiltration hole, ring infiltrometer, and piezometer, which evaluated the characteristics of soil in its natural condition. Through the investigations two layers (layers 1 and 2) were identified in this area. Layers 1 are more superficial, and constituted of horizon A and finally horizon B. In the lower layer 2 (horizon C), with a reddish colour, the soil shows characteristics of alteration of sedimentary rocks. The results of in situ tests k show similar values between each other, because the infiltration tests have values of k in the order of 10-5 m/s, in the same order of magnitude as the results with piezometer in layer 1. The values of k of layer 2 were in the order of 10-7 and 10-8 m/s in the natural state. The compacted samples had values of k in the order 10-9 and 10-10 m/s. The results of k in the flexible wall permeameter were higher for undisturbed samples, and compacted samples resulted in values in the order of 10-9 m/s. Values of k of this order are indicated as natural impermeabilizing barriers in sanitary land-fills.